The AKP'S proposal for a "Turkish type of presidentialism" in comparative context. (2nd January 2016) - Özsoy Boyunsuz, Şule
ABSTRACT: President Recep T. Erdoğan and the Justice and Development Party have proposed a presidential system with a very strong single executive with very little or no constitutional constraints, called "the Turkish Type of Presidential System." They campaigned for it from 2013 through the 2015 parliamentary election. Even though this proposal has not been enacted, it has shaped Turkish politics considerably by generating strong opposition as well as stalwart defenders. This article examines the constitutional institutions of the proposed presidential model, compares it with other known examples of presidential systems, and argues that it is a form of hyper-presidentialism.